Exporting to the Federal Republic of Germany - Klaus Boeck (Intereconomics, 1974)
Among Industrialised countries, the Federal Republic is certainly one of the largest markets able to absorb vast quantities of products from the LDCs of South East Asia. However, to open up this sales outlet with its formidable future, it will be necessary to operate an all-embracing marketing strategy.
Keywords: 330; Foreign Trade